Undocumented migrants and healthcare : eight stories from Switzerland - Jossen, Marianne (Open Reports series ;, 2018)
"What do undocumented migrants experience when they try to access healthcare? How do they navigate the (often contradictory) challenges presented by bureaucratic systems, financial pressures, attitudes to migrants, and their own healthcare needs? This urgent study uses a grounded theory approach to explore the ways in which undocumented migrants are included in or excluded from healthcare in a Swiss region. Marianne Jossen explores the ways migrants try to obtain healthcare on their own, with the help of NGOs or via insurance, and how they cope if they fail, whether by using risky strategies to access healthcare or leaving serious health issues untreated. Jossen shows that even for those who succeed, inclusion remains partial and fraught with risks. Based on interviews with migrants, health practitioners and NGO staff and using a rigorous academic approach, Undocumented Migrants and Healthcare is an important contribution to a vital contemporary issue. It is necessary reading for researchers in Public Health and Migration Studies, as well as government and non-governmental organisations in Switzerland and beyond. It will be of interest to anyone concerned with healthcare and migration in the twenty-first century."--Publisher's website